Animal models to explore cardiovascular disease - Merkel, Martin (Henry Stewart Talks, 2008)
Atherosclerosis is a complex disease involving several different molecular and cellular mechanisms in its pathogenesis, For its experimental investigation, usually higher animals as mammals need to be employed, Here, the animal models currently used in atherosclerotic research are reviewed und their respective advantages and disadvantages are depicted, Use of inbred mouse strains and different genetically modified mice, The main disparities between mouse and human lipid metabolism, Considerations and techniques to create useful animal models